AN ANALYSIS OF STUDENTS’ GRAMMATICAL ERRORS IN WRITING REPORT TEXT AT NINETH GRADE SMPN 1 TEMBILAHAN HULU - Cessy Herandani; Samsul Amri; Syafrizal (Program Studi Pendidikan Bahasa Inggris, 2022)
The aims of this study are intended to find out the types of grammatical errors that are often made by students in writing report texts. The design was a descriptive method. Documentation of students’ report texts was used to collect the data. The subjects of this study were the students in the IX grade of SMPN 1 Tembilahan Hulu. According to the findings, the highest percentage of grammatical errors that students frequently make is in accordance with omission with 36.7%, followed by missing orders with 8.9%, missing information with 4.4%, and error addition with 2.2%.